2021
DOI: 10.3390/pharmaceutics13040528
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Accuracy of Oral Extemporaneous Suspensions of Antibiotics: Measuring Procedures and Administration Devices

Abstract: Extemporaneous suspensions are often marketed with several administration devices that can be freely used by patients/caregivers. The homogeneity of suspensions requires shaking before use. Hence, it is crucial to assess the precision of all devices and the users’ awareness of the shaking procedure. This study was conducted at University Institute Egas Moniz with 40 pharmacy students who were asked to measure 2.5 and 5 mL of two extemporaneous azithromycin suspensions. Formulation A is marketed with a double-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The type of dosing device can affect dosing accuracy and studies have shown that using a syringe is generally better than a cup, dropper or spoon to accurately dispense a dose [47][48][49][50] but the suitability of a dosing device was also shown to be dependent on the viscosity of the liquid [47]. Furthermore, dosing accuracy is also related to consumer use and education of the consumer on the correct way to use a dosing device [47][48][49][50]. A high dosing accuracy of the formulation together with a, for the formulation, suitable dosing device is crucial in order ensure that a correct dose is administered [51,52].…”
Section: Dispensed Dose and Dosing Accuracymentioning
confidence: 99%
“…The type of dosing device can affect dosing accuracy and studies have shown that using a syringe is generally better than a cup, dropper or spoon to accurately dispense a dose [47][48][49][50] but the suitability of a dosing device was also shown to be dependent on the viscosity of the liquid [47]. Furthermore, dosing accuracy is also related to consumer use and education of the consumer on the correct way to use a dosing device [47][48][49][50]. A high dosing accuracy of the formulation together with a, for the formulation, suitable dosing device is crucial in order ensure that a correct dose is administered [51,52].…”
Section: Dispensed Dose and Dosing Accuracymentioning
confidence: 99%
“…Most studies on dosing devices describe dosing accuracy by caregivers [ 15 , 17 , 18 ]. In terms of dosing by caregivers, previous research has generated varied conclusions on measuring spoon accuracy.…”
Section: Introductionmentioning
confidence: 99%